The Existence of Religious Traditions of the Wonosari Village Community in Starting the Civilization of Social Life: Analysis of Emile Durkheim's Mechanical Solidarity Theory - Rini Rahmawati; Maulana Ihsyan Azwar; M. Rizky Alif S; Aang Asari (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Puwon Hamlet is one of the seven hamlets in Wonosari Village, Patebon Subdistrict, Kendal Regency. Various cultural activities from each hamlet in Wonosari Village still exist today. This research uses a field research method by going directly to the graves of Kyai and Nyai Cablik located in Puwon Hamlet, precisely RT 5 / RW 6 and stands on land not far from the public cemetery with land conditions higher than residents' houses. The results of this study when analyzed with Emile Durkheim's mechanical solidarity theory are the discovery of several types of traditional social life that still exist in Wonosari Village.